Hemorrhagic Complications of Paracentesis: A Systematic Review of the Literature. (16th December 2014) - Sharzehi, Kaveh; Jain, Vishal; Naveed, Ammara; Schreibman, Ian
Abstract : Introduction . Large volume paracentesis is considered a safe procedure carrying minimal risk of complications and rarely causing morbidity or mortality. The most common complications of the procedure are ascitic fluid leakage, hemorrhage, infection, and perforation. The purpose of this study was to evaluate all hemorrhagic complications and their outcomes and to identify any common variables. Methods . A literature search for all reported hemorrhagic complications following paracentesis was conducted. A total of 61 patients were identified. Data of interest were extracted and analyzed. The primary outcome of the study was 30-day mortality, with secondary endpoints being achievement of hemostasis after intervention and mortality based on type of intervention. Results . 90% of the patients undergoing paracentesis had underlying cirrhosis. Three types of hemorrhagic complications were identified: abdominal wall hematomas (52%), hemoperitoneum (41%), and pseudoaneurysm (7%). Forty percent of the patients underwent either a surgical (35%) or an IR guided intervention (65%). Patients undergoing a surgical intervention had a significantly higher rate of mortality at day 30 compared to those undergoing IR intervention. Conclusion . Abdominal wall hematomas and hemoperitoneum are the most common hemorrhagic complications of paracentesis. Transcatheter coiling and embolization appear to be superior to both open and laparoscopic surgery in treatment of these complications.